Heterogeneous sensor-based rotor attitude detection for a spherical motor using distributed Kalman filtering method - Sili Zhou; Guoli Li; Qunjing Wang; Jiahu Guo; Yuanyuan Jiang; Jiazi Xu (AIP Advances)
Permanent magnet spherical motors (PMSpMs) are new special motors with multiple degrees of freedom capability in a limited space. This paper proposes a heterogeneous sensor-based rotor attitude detection (RAD) approach for the PMSpM using the distributed Kalman filtering method. An industrial camera is used to detect the rotor attitude by integrating the Kalman filter (visual method), in order to improve short-time occlusion ability. Meanwhile, a MEMS sensor is introduced to detect the PMSpM rotor attitude simultaneously by using the Kalman filtering method (MEMS method). On the basis of this, the heterogeneous sensor network consists of the camera and the MEMS sensor, and the proposed RAD approach is implemented through the Kalman filtering fusing method. To verify the proposed heterogeneous sensor-based RAD method, the test bench is developed and the one-dimensional and three-dimensional fusing experiments are conducted. The results indicate that the heterogeneous sensor-based RAD method possesses the ability of visual resistance to long-term interference with good accuracy.